ANALYSIS OF INTERNAL AND EXTERNAL FACTORS IN RELATION TO FATIGUE AND SLEEPINESS LEVELS ON NURSES OF Dr. HASAN SADIKIN BANDUNG CENTRAL GENERAL HOSPITAL - Mentari Pujiasningrum, Sahnaz
Nursing is a vital part of a hospital where nurses play an important role in providing safe and quality services, which impacts on comfort, healing, and patient satisfaction. It is known that nurses experience fatigue, injury, and stress at high risk leading to medication errors and potentially getting infections from patients. Lack of sleep time and circadian phase misalignments during shift work are associated with increased levels of errors in performing nursing duties. Research on the relationship between fatigue and sleepiness in nurses of Dr. Hasan Sadikin Bandung (RSHS) has never been conduct, where almost 40% (1,163 personnel) of the RSHS staff work as nurses. This cross-sectional study aims to determine the relationship between internal factors (age, sleep quantity, length of work) and external factors (work shifts, work patterns, and duration of work) with the fatigue and sleepiness level in inpatient instalation in Kemuning building of RSHS. This research method was conducted by interview and questionnaire distribution, The validity test using SPSS 25.0 gave valid results for each question item. Fatigue feeling is identified by KAUPK2, symptoms of fatigue are identified by IFRC, the level of fatigue using FSS, chronotype using MEQ, the level of sleepiness using ESS and the average sleep time is measured by Thurstone Scale, with reliability values are 0.865, 0.946, 0.918, 0.823, 0.699, 0.659, for 48 respondents. The results showed 18.75% of respondents experienced a very tired level of fatigue, with the most symptoms of fatigue is the mind becomes chaotic, tired in the legs, and really want to lie down, where 62.5% of respondents have a significant level of fatigue. 70.8% of respondents have a morning chronotype, 50% of respondents are indicated to have excessive sleepiness, with average sleepiness peak time of morning shift at 10-11 a.m, afternoon shift at 6-7 p.m., and 3 a.m. for night shift. Univariate analysis using normality test, bivariate using Pearson test and Spearman’s rank, and multiple regression using t-test and F-test showed there was a strong relationship between sleep quantity and fatigue level (sig. = 0,000 <0.05; correlation coeff. = 0.612) and duration of work with sleepiness (sig. = 0,000 <0.05; correlation coeff. = 0.819).